A Picture is Worth a Thousand Mental Models: Evaluating Human Understanding of Robot Teammates. (September 2013) - Ososky, Scott; Philips, Elizabeth; Schuster, David; Jentsch, Florian
Across the domains in which robots are prevalent, it is possible to imagine many different forms and functions of robots. The purpose of this investigation was to gain a better understanding of the scope and type of a priori knowledge structures humans hold of robots, among novice users of robotic systems. Participant mental models of a hypothetical robot in a military team scenario were elicited along the dimensions of form and function, taking prior individual experiences into consideration. Participants who conceived a robot with anthropomorphic or zoomorphic qualities reported more perceived knowledge of their robotic teammate, as well as of their human–robot team. Participants who had more experience with video games also believed that they had more knowledge of their imagined robot and their human–robot team. Insight into novice users' understanding of robots has implications for HRI design and training.